Assessing the impact of solar PV on vegetation growth through ground sunlight distribution at a solar farm in Aotearoa New Zealand - Dhlamini, Matlotlo; Brent, Alan (Archives of Sustainable Energy Systems, 2025)
The global shift toward renewable energy has positioned solar photovoltaics (PV) as central to sustainable development. However, the land demands of ground-mounted PV systems raise concerns about competition with agriculture, particularly in regions with limited or productive farmland. Agrivoltaics, which integrates solar energy generation with agricultural use, offers a potential solution. While agrivoltaics has been extensively studied in arid and semi-arid climates, little is known about its feasibility and impacts in temperate environments such as Aotearoa New Zealand, particularly the effects of PV-induced shading on ground-level light availability and vegetation. This study modelled the spatial and seasonal distribution of ground-level irradiation and Photosynthetic Photon Flux Density (PPFD) beneath fixed-tilt PV arrays at Tauhei Solar Farm in the Waikato region. Using 2018 hourly SolarGIS data and a Python-based simulation, the research accounts for solar geometry, panel shading, and irradiance decomposition. It quantifies and maps PPFD to evaluate light conditions and its implications for vegetation growth. Results reveal significant spatial and temporal variation in PPFD. In summer, midday inter-row areas exceeded 450 μmol/m²/s, while winter under-panel zones often fell below 100 μmol/m²/s—near the light compensation point for many shade-sensitive plants. This variation supports a precision agrivoltaic strategy that zones land based on irradiance levels. By aligning crop types and planting schedules with seasonal light profiles, land productivity and ecological value can be improved. Spring and summer favour high-light crops, while winter is more suitable for shade-tolerant species or grazing. These findings are highly applicable in Aotearoa New Zealand’s pasture-based systems and show that effective light management is critical for agrivoltaic success in temperate climates.